2021
DOI: 10.1111/acer.14573
|View full text |Cite
|
Sign up to set email alerts
|

Network Meta‐Analysis on the Mechanisms Underlying Alcohol Augmentation of COVID‐19 Pathologies

Abstract: Background The coronavirus disease 2019 (COVID‐19) pandemic is a worldwide crisis caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Many COVID‐19 patients present with fever in the early phase, with some progressing to a hyperinflammatory phase. Ethanol (EtOH) exposure may lead to systemic inflammation. Network meta‐analysis was conducted to examine possible relationships between EtOH consumption and COVID‐19 pathologies. Methods Molecules affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…Furthermore, Aβ plaque buildup could occur naturally over time, and CAA symptoms have been reported to naturally bolster with age (Biffi and Greenberg 2011 ). Aging has been identified as a neuroinflammatory process; neuroinflammation is known to lead to the onset and progression of neurodegenerative diseases, including AD (McManus and Heneka 2017 ; Bossù et al 2020 ; Huang et al 2021b ). Moreover, it has been reported that the number of naïve T-cells decreases with age, which is thought to be one of the factors contributing to a decreased capacity to induce an immune response following new infections (McManus and Heneka 2017 ); moreover, AD patients have also been reported to have significantly low levels of naïve T-cells (McManus and Heneka 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Aβ plaque buildup could occur naturally over time, and CAA symptoms have been reported to naturally bolster with age (Biffi and Greenberg 2011 ). Aging has been identified as a neuroinflammatory process; neuroinflammation is known to lead to the onset and progression of neurodegenerative diseases, including AD (McManus and Heneka 2017 ; Bossù et al 2020 ; Huang et al 2021b ). Moreover, it has been reported that the number of naïve T-cells decreases with age, which is thought to be one of the factors contributing to a decreased capacity to induce an immune response following new infections (McManus and Heneka 2017 ); moreover, AD patients have also been reported to have significantly low levels of naïve T-cells (McManus and Heneka 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…These 11 mediators were mapped to the pathways predicated to associate with SARS-CoV-2 infection. In summary, despite medical records of COVID-19 patients being sparse for drinking history, our meta-analyses demonstrated that alcohol exposure could augment COVID-19 pathologies (Huang et al 2021).…”
Section: Discussionmentioning
confidence: 79%
“…First, as more progress is made on the understanding of COVID-19 and obesity, more molecules and relationships will be identified, which will improve the comprehensiveness of COVID-19and PA-associated molecules in QIAGEN's QKB database for IPA analysis. Secondly, IPA analysis gives all the molecules in the pathway an equal weight without taking into account the varied significance of different molecules or whether the molecule is inherent to the interactions [70]. Finally, considering the importance of elevated levels of free fatty acids (FFAs) in obesogenic pathologies [23,24], this study focused on the analysis of PA and n-3 fatty acids on the pathogenesis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…IPA Core Analysis was used to identify the most significant biological canonical pathways that the molecules in the dataset are involved in [70,74]. Statistical analysis was performed using Fisher's exact test with the Benjamini-Hochberg method of multiple testing correction to assess which biological attributes, such as a pathway or biological function, were significantly associated with the genes in the dataset [75].…”
Section: Ipa Analysismentioning
confidence: 99%